The role of islamic philanthropic institutions in overcoming the economic turbulence of pre-welfare communities in the covid-19 pandemic situation - Marwini Marwini (Indonesian Journal of Islamic Economics Research, 2021)
The number of poor people has increased due to economic uncertainty in the Covid-19 pandemic. This study aims to analyze the impact of Covid-19 on the Indonesian economy and the role of Islamic philanthropic institutions in overcoming poor people in the Covid-19 situation. This research was conducted by collecting primary data from several professional zakat institutions in Semarang, Central Java using observation and interview methods. The data collected in this study were analyzed using NVivo 11 data processing software. The findings of this study include the impact of Covid-19 on the Indonesian economy through a decrease in the ability of industries or companies to employ employees, resulting in a decrease in household income and a decrease in purchasing power of consumers in the aggregate. Another finding is the role of Islamic philanthropic institutions in overcoming pre-prosperous communities in the midst of Covid-19 through charity programs and empowerment programs.